(3NHQ GHf LdLds - (3fbd eLghds ((3HjQhJ s)
(3ChdgG (B:s
(3bGd GHf CHj CUjHYg ai cJGHg GdeJVef CNHGQ CWHGA GdYQH (B: (3EHf LdLd gh CHhOGhO SdjeGf Hf MSGf s
(3BNQgG (B:s
(3cJGH GdeOgT aj CNHGQ GdMjhGf cJGH GdKeGfjI ai GefWb hgh GdJUfja GdhSW s
(3Vef eLehY , JQJjHgG (B: (3ef U (B410 - (3U(B418s
(3ofbd ef cJGH GHf CHj CUjHYIs
(3fbd ef cJGH GHf CHj CUjHYI (B( (3Yjhf GdCfHGA aj WHbGJ GdCWHGA(B)s
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B197 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B47 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B96s
Keywords: (3GdJGQjNs